Incidence of anaemia among the female tea garden workers in a tea plantation in upper Assam, India - Das, Bhaskar; Sengupta, Bani; Chakrabarti, Sila; Rudra, Tapas; Sengupta, Sarthak (Journal of the Indian Medical Association, 2012)
Nutritional anaemia is the most common type and cause of anaemia. Tea garden workers constitute approximately 1/5th of population in the state of Assam. Reports indicate higher prevalence of undernutrition in this population. The present study was designed to focus on the incidence of anaemia among the female tea garden workers and to examine the effect of iron with vitamin B12 and folic acid supplementation in them. Two hundred and forty-four female tea garden workers who could be persuaded to participate in the study were sampled for haemoglobin typing by agarose gel electrophoresis (pH 8.9). Their haematological parameters were measured on automated cell counter to read Hb, RBC, MCV, MCH and MCHC. BMI was calculated from weight/height in metre2. The study revealed 182 anaemic (<11.0 g/dl) subjects which included 32 cases of hereditary anaemia and 150 cases of nutritional anaemia. Iron supplementation for duration of 3 months was given to 150 workers out of total 182 subjects who had haemoglobin <11.0 g/dl. Thirteen subjects with haemoglobin >11.0 g/dl were studied as controls. Level of haemoglobin was rechecked after 3 months by Sahli's method. Based on the size of red blood cells it was observed that the workers suffered from all three forms of anaemia viz, microcytic, normocytic and macrocytic. There was a significant rise in haemoglobin concentration when the anaemic individuals took iron with vitamin B12 and folic acid supplement for three consecutive months supported by two doses of anthelminthic drug. The present study showed that nutritional anaemia is a major problem in the female tea garden workers and arrangement of supplementation therapy is utmost necessary to improve their general condition and work efficiency.